2018
DOI: 10.1038/s41467-018-04592-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal relays control layer identity of direction-selective neuron subtypes in Drosophila

Abstract: Visual motion detection in sighted animals is essential to guide behavioral actions ensuring their survival. In Drosophila, motion direction is first detected by T4/T5 neurons. Their axons innervate one of the four lobula plate layers. How T4/T5 neurons with layer-specific representation of motion-direction preferences are specified during development is unknown. We show that diffusible Wingless (Wg) between adjacent neuroepithelia induces its own expression to form secondary signaling centers. These activate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 70 publications
(98 reference statements)
4
63
0
Order By: Relevance
“…Consistent with our scRNAseq analysis, a previous study found dac and omb to be expressed in postmitotic, developing T4/T5a,b and T4/T5c,d neurons, respectively (Fig. 4B,E) (Apitz and Salecker, 2018). Our scRNA-seq analysis further revealed that ab was specific to T4/T5a,b (Fig.…”
Section: Grain Acts As Part Of Two Combinations Of Transcription Factsupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with our scRNAseq analysis, a previous study found dac and omb to be expressed in postmitotic, developing T4/T5a,b and T4/T5c,d neurons, respectively (Fig. 4B,E) (Apitz and Salecker, 2018). Our scRNA-seq analysis further revealed that ab was specific to T4/T5a,b (Fig.…”
Section: Grain Acts As Part Of Two Combinations Of Transcription Factsupporting
confidence: 91%
“…Based on the previously reported subtype-specific marker genes optomotor-blind (omb) and dachshund (dac) (Apitz and Salecker, 2018), we assigned clusters to one of the following subtype-pairs: T4a,b, T5a,b, T4c,d or T5c,d (Fig. 3B, Fig.…”
Section: Each Of the Four T4 And T5 Subtypes Has A Unique Transcriptimentioning
confidence: 99%
See 3 more Smart Citations